KONSISTENSI EFISIENSIi BANK PEMBIAYAAN RAKYAT SYARIAH BPRS) DI JAWA TIMUR PADA TAHUN 2016-2021 MENGGUNAKAN DATAi ENVELOPMENT ANALYSIS (DEA) - Andriani Samsuri (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aimed to determine the consistency efficiency level employed of Islamic People's Financing Banks in East Java during 2016-2021. The research of descriptive research type with a quantitative approach. The samples of in this study were all Islamic People's Financing Banks registered with the OJK and reporting financial publications on the OJK official website during 2016-2021. Which were 21 BPRS. Data were collected from the OJK official website. This study uses the Data Envelopment Analysis (DEA) method with the assumption of Variable Return to Scale (VRS) model using Banxia Frontier Analysis software. The results of this study indicated that simultaneously BPRS in East Java during 2016-2021 were categorized as inefficient. This was because the BPRS was considered still unable to contribute input and output variables optimally consistency.